A straightforward entry to chiral carbocyclic nucleoside analogues via the enantioselective [3+2] cycloaddition of α-nucleobase substituted acrylates1. Issue 62 (11th August 2015) - Xie, Ming-Sheng; Wang, Yong; Li, Jian-Ping; Du, Cong; Zhang, Yan-Yan; Hao, Er-Jun; Zhang, Yi-Ming; Qu, Gui-Rong; Guo, Hai-Ming
<x xml:space="preserve">Abstract</x> A straightforward entry to chiral carbocyclic nucleoside analogues is achieved via the enantioselective [3+2] cycloaddition of α-nucleobase substituted acrylates to vinyl cyclopropanes.